The mitochondrial Ca2+ channel MCU is critical for tumor growth by supporting cell cycle progression and proliferation - Fernandez Garcia, Emily; Paudel, Usha; Noji, Michael C.; Bowman, Caitlyn E.; Rustgi, Anil K.; Pitarresi, Jason R.; Wellen, Kathryn E.; Arany, Zolt; Weissenrieder, Jillian S.; Foskett, J. Kevin (Frontiers in Cell and Developmental Biology, 2023)
Introduction: The mitochondrial uniporter (MCU) Ca2+ ion channel represents the primary means for Ca2+ uptake by mitochondria. Mitochondrial matrix Ca2+ plays critical roles in mitochondrial bioenergetics by impinging upon respiration, energy production and flux of biochemical intermediates through the TCA cycle. Inhibition of MCU in oncogenic cell lines results in an energetic crisis and reduced cell proliferation unless media is supplemented with nucleosides, pyruvate or α-KG. Nevertheless, the roles of MCU-mediated Ca2+ influx in cancer cells remain unclear, in part because of a lack of genetic models. Methods: MCU was genetically deleted in transformed murine fibroblasts for study in vitro and in vivo. Tumor formation and growth were studied in murine xenograft models. Proliferation, cell invasion, spheroid formation and cell cycle progression were measured in vitro. The effects of MCU deletion on survival and cell-death were determined by probing for live/death markers. Mitochondrial bioenergetics were studied by measuring mitochondrial matrix Ca2+ concentration, membrane potential, global dehydrogenase activity, respiration, ROS production and inactivating-phosphorylation of pyruvate dehydrogenase. The effects of MCU rescue on metabolism were examined by tracing of glucose and glutamine utilization for fueling of mitochondrial respiration. Results: Transformation of primary fibroblasts in vitro was associated with increased MCU expression, enhanced MCU-mediated Ca2+ uptake, altered mitochondrial matrix Ca2+ concentration responses to agonist stimulation, suppression of inactivating-phosphorylation of pyruvate dehydrogenase and a modest increase of mitochondrial respiration. Genetic MCU deletion inhibited growth of HEK293T cells and transformed fibroblasts in mouse xenograft models, associated with reduced proliferation and delayed cell-cycle progression. MCU deletion inhibited cancer stem cell-like spheroid formation and cell invasion in vitro, both predictors of metastatic potential. Surprisingly, mitochondrial matrix [Ca2+], membrane potential, global dehydrogenase activity, respiration and ROS production were unaffected. In contrast, MCU deletion elevated glycolysis and glutaminolysis, strongly sensitized cell proliferation to glucose and glutamine limitation, and altered agonist-induced cytoplasmic Ca2+ signals. Conclusion: Our results reveal a dependence of tumorigenesis on MCU, mediated by a reliance on MCU for cell metabolism and Ca2+ dynamics necessary for cell-cycle progression and cell proliferation.